Яруу найраг бүтээх уламжлалт туршлагад хийсэн ажиглалт - Бигэрмаа, Р. (Acta Mongolica, 2005)
Drawing a conclusion, B Lhagvasuren a poet used the oriental tradition in his works. Also natural Leature is observed from almos poems of his. It can be easy to understand for mongolian people.